The Delivery of Multipotent Adult Progenitor Cells to Extended Criteria Human Donor Livers Using Normothermic Machine Perfusion - Laing, Richard W.; Stubblefield, Samantha; Wallace, Lorraine; Roobrouck, Valerie D.; Bhogal, Ricky H.; Schlegel, Andrea; Boteon, Yuri L.; Reynolds, Gary M.; Ting, Anthony E.; Mirza, Darius F.; Newsome, Philip N.; Mergental, Hynek; et al. (Frontiers in Immunology, 2020)
Background Pre-clinical research with multi-potent adult progenitor cells (MAPC® cells, Multistem, Athersys Inc., Cleveland, Ohio) suggests their potential as an anti-inflammatory and immunomodulatory therapy in organ transplantation. Normothermic machine perfusion of the liver (NMP-L) has been proposed as a way of introducing therapeutic agents into the donor organ. Delivery of cellular therapy to human donor livers using this technique has not yet been described in the literature. The primary objectives of this study were to develop a technique for delivering cellular therapy to human donor livers using NMP-L and demonstrate engraftment. Methods Six discarded human livers were perfused for 6 hours at 37°C using the Liver Assist (Organ Assist, Groningen). 50x106 CMPTX-labelled MAPC cells were infused directly into the right lobe via the hepatic artery (HA, n=3) or portal vein (PV, n=3) over twenty minutes at different time points during the perfusion. Perfusion parameters were recorded and central and peripheral biopsies were taken at multiple time-points from both lobes and subjected to standard histological stains and confocal microscopy. Perfusate was analysed using a 35-plex multiplex assay and proteomic analysis. Results There was no adverse effect on perfusion flow parameters on infusion of MAPC cells by either route. Three out of six livers met established criteria for organ viability. Confocal microscopy demonstrated engraftment of MAPC cells across vascular endothelium when perfused via the artery. 35-plex multiplex analysis of perfusate yielded 13 positive targets, 9 of which appeared to be related to the infusion of MAPC cells (including Interleukin’s 1b, 4, 5, 6, 8, 10, MCP-1, GM-CSF, SDF-1a). Proteomic analysis revealed 290 unique proteins in the perfusate from time-points following the infusion of cellular therapy, many of which have strong links to MAPC cells and mesenchymal stem cells in the literature. Functional enrichment analysis demonstrated their immunomodulatory potential Conclusion We have demonstrated that cells can be delivered directly to the target organ, prior to host immune cell population exposure and without compromising the perfusion. Transendothelial migration occurs following arterial infusion. MAPC cells secrete a host of soluble factors that would have anti-inflammatory and immunomodulatory benefits in a human model of liver transplantation.